Financial and relational impact of having a boy with posterior urethral valves - Harper, Luke; Botto, Nathalie; Peycelon, Matthieu; Michel, Jean-Luc; Leclair, Marc-David; Garnier, Sarah; Clermidi, Pauline; Arnaud, Alexis; Dariel, Anne; Dobremez, Eric; Faure, Alice; Fourcade, Laurent; et al. (Frontiers in Pediatrics, 2023)
Introduction: Childhood chronic diseases affect family functioning and well-being. The aim of this study was to measure the impact of caring for a child with PUV, and the factors that most impact the burden of care.Patients and method: We gave a questionnaire on the familial impact of having a child with posterior urethral valves to all parents of a child included in the CIRCUP trial from 2015 onwards. The questionnaire included questions about the parents' demographics, health, professional, financial and marital status and how these evolved since the child's birth as well as the "impact on family scale" (IOFS) , which gives a total score ranging from 15 (no impact) to 60 (maximum impact). We then analyzed both the results of the specific demographic questions as well as the factors which influenced the IOFS score.Results: We retrieved answers for 38/51 families (74.5% response rate). The average IOFS score was 23.7 (15 to 51). We observed that the child's creatinine level had an effect on the IOFS score (p=0.02), as did the parent's gender (p=0.008), health status (p=0.015), being limited in activity since the birth of the child (p=0.020), being penalized in one's job (p=0.009), being supported in one's job (p=0.002), and decreased income (p=0.004). Out of 38 mother/father binomials, 8/33 (24.2%) declared that they were no longer in the same relationship afterwards.In conclusion, having a boy with PUV significantly impacts families. The risk of parental separation and decrease in revenue is significant. Strategies aiming to decrease these factors should be put in place as soon as possible.